2015
DOI: 10.1128/mbio.01714-15
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro CRISPR/Cas9 System for Efficient Targeted DNA Editing

Abstract: The clustered regularly interspaced short palindromic repeat (CRISPR)/CRISPR-associated protein 9 (Cas9) system, an RNA-guided nuclease for specific genome editing in vivo, has been adopted in a wide variety of organisms. In contrast, the in vitro application of the CRISPR/Cas9 system has rarely been reported. We present here a highly efficient in vitro CRISPR/Cas9-mediated editing (ICE) system that allows specific refactoring of biosynthetic gene clusters in Streptomyces bacteria and other large DNA fragments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
58
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 44 publications
0
58
0
Order By: Relevance
“…The booming technology‐clustered regularly interspaced short palindromic repeats (CRISPR) system has developed rapidly over the last decade (Bayat, Modarressi, & Rahimpour, ; Ferreira, David, & Nielsen, ; Hille et al, ; Sander & Joung, ). The widely used CRISPR‐Cas9 from Streptococcus pyogenes has been designed and optimized to facilitate molecular cloning (W. Jiang et al, ; Kang, Charlop‐Powers, & Brady, ; Liu et al, ; H. Wang et al, ), such as CATCH (Cas9‐Assisted Targeting of Chromosome) (W. Jiang et al, ), ICE (in vitro CRISPR/Cas9‐mediated Editing; Liu et al, ) and exoCET (exonuclease Combined with RecET recombination; H. Wang et al, ). All these strategies are successfully used in large DNA construct cloning or modification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The booming technology‐clustered regularly interspaced short palindromic repeats (CRISPR) system has developed rapidly over the last decade (Bayat, Modarressi, & Rahimpour, ; Ferreira, David, & Nielsen, ; Hille et al, ; Sander & Joung, ). The widely used CRISPR‐Cas9 from Streptococcus pyogenes has been designed and optimized to facilitate molecular cloning (W. Jiang et al, ; Kang, Charlop‐Powers, & Brady, ; Liu et al, ; H. Wang et al, ), such as CATCH (Cas9‐Assisted Targeting of Chromosome) (W. Jiang et al, ), ICE (in vitro CRISPR/Cas9‐mediated Editing; Liu et al, ) and exoCET (exonuclease Combined with RecET recombination; H. Wang et al, ). All these strategies are successfully used in large DNA construct cloning or modification.…”
Section: Introductionmentioning
confidence: 99%
“…The widely used CRISPR-Cas9 from Streptococcus pyogenes has been designed and optimized to facilitate molecular cloning (W. Jiang et al, 2015;Kang, Charlop-Powers, & Brady, 2016;Liu et al, 2015;H. Wang et al, 2018), such as CATCH (Cas9-Assisted Targeting of Chromosome) (W. Jiang et al, 2015), ICE (in vitro CRISPR/Cas9-mediated Editing; Liu et al, 2015) and exoCET (exonuclease Combined with RecET recombination; H. Wang et al, 2018). All these strategies are successfully used in large DNA construct cloning or modification.…”
mentioning
confidence: 99%
“…A system called CRISPRi was recently applied to S. coelicolor , which used a catalytically dead Cas9 (dCas9) to interfere with gene expression in a sequence-specific manner [22], and thus can be potentially applied to repress transcription of negative/positive regulatory genes for discovery of natural products from silent BGCs. Other tools such as the in vitro DNA editing system [23] and the transformation-associated recombination (TAR) method [24 • ] were also established based on the versatile CRISPR/Cas9 system, which further advances technological development in natural product discovery. Successful application of the CRISPR/Cas9 system in fungi has also been reported [25] and reviewed previously [26].…”
Section: Activation Of Silent Bgcs In Native Hostsmentioning
confidence: 99%
“…Compared to regular methods that deliver plasmids or mRNA encoding Cas9, increasing studies demonstrated that direct delivery of Cas9 RNP for genome editing in cells and animals has obvious advantages 17-20 , such as reduced off-target effects, low toxicity, high editing efficiency, etc. Therefore, a large amount of biopharmaceutical companies and research institutes have recently put greater emphasis on developing Cas9 RNP-based gene therapy medicines.To produce Cas9 RNP, the routine strategy needs to obtain Cas9 and sgRNAs separately and then assemble them in vitro [21][22][23] . During the process, Cas9 is generally purified by recombinant expression from E. coli, whereas sgRNAs are constructed either by in vitro transcription that often requires tedious steps, or by chemical synthesis which is time consuming and expensive.…”
mentioning
confidence: 99%
“…To produce Cas9 RNP, the routine strategy needs to obtain Cas9 and sgRNAs separately and then assemble them in vitro [21][22][23] . During the process, Cas9 is generally purified by recombinant expression from E. coli, whereas sgRNAs are constructed either by in vitro transcription that often requires tedious steps, or by chemical synthesis which is time consuming and expensive.…”
mentioning
confidence: 99%